2004
DOI: 10.1680/grim.2004.8.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Effect of material properties on the behaviour of sand—cement—fibre composites

Abstract: Saturated drained triaxial compression tests with local strain measurement were carried out to evaluate the effects of using three different randomly distributed fibres (polyester,polypropylene and glass fibres) and rapid hardening Portland cement to improve the engineering behaviour of a uniform fine sand. In addition to the nature of the fibres,also analysed have been the separate and combined effect of fibre content (up to 0·5% by weight), fibre length (up to 36 mm), cement content (from 0% to 7% by weight)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(22 citation statements)
references
References 29 publications
0
13
0
9
Order By: Relevance
“…50% by weight of the sum of dry soil and cement. The selection of fibre type, percentage and dimensions followed studies by Consoli et al (2004Consoli et al ( , 2007b.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…50% by weight of the sum of dry soil and cement. The selection of fibre type, percentage and dimensions followed studies by Consoli et al (2004Consoli et al ( , 2007b.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, studies on reinforcing sand by the inclusion of fibre have also been reported (Ahmed, 2012;Casagrande et al, 2006;Consoli et al, 2007bConsoli et al, , 2007cConsoli et al, , 2009e, 2009f, 2012dIbraim et al, 2010;Maher and Gray, 1990;Santos et al, 2010aSantos et al, , 2010b. Few studies have been carried out on the influence of fibre inclusion on the mechanical behaviour of cemented soil (Ahmed et al, 2011;Consoli et al, 1998Consoli et al, , 2002Consoli et al, , 2004Maher and Ho, 1993;Santos et al, 2010b;Tang et al, 2007). Usually the fibre-reinforced cemented soil strength is assessed by numerous laboratory tests (e.g., unconfined compression, splitting tensile and triaxial tests) that aim to find the minimum amount of cement that meet the target property.…”
Section: Introductionmentioning
confidence: 99%
“…Osorio sand was chosen due to its widely known behavior and extensive investigation in the past 20 years at the Federal University of Rio Grande do Sul (UFRGS, Brazil) using distinct laboratory testing, such as plate load tests (Casagrande, 2001, Consoli et al, 2003a, Spinelli, 1999, ring shear tests (Casagrande, 2005, Consoli et al, 2003b, direct shear tests (Marcon, 2005), isotropic compression tests (Consoli et al, 2005) and triaxial compression tests (Consoli et al, 1998, 2002, 2004, Festugato 2008, 2011, Sachetti, 2014.…”
Section: Materials and Specimen Preparationmentioning
confidence: 99%
“…The fibre content used in the experiments was 0?5% by weight of dry solids. Previous studies (Consoli et al, 2004(Consoli et al, , 2009(Consoli et al, , 2011b have shown that these fibre characteristics optimise workability and improve the mechanical behaviour for different types of soil. As no other study has ever been carried out on fibre-reinforced mine tailings, these characteristics were taken as the initial reference, and worked satisfactorily.…”
Section: Fibresmentioning
confidence: 99%